2012
DOI: 10.1071/rs12038
|View full text |Cite
|
Sign up to set email alerts
|

The Mallee fire and biodiversity project

Abstract: Fire is a widespread disturbance and an important ecological process in semi-arid mallee ecosystems of southern Australia. Understanding the effects of fire on plants and animals is a key challenge for the conservation and management of biodiversity in this ecosystem. Commencing in 2006, the Mallee Fire and Biodiversity Project is investigating the effects of fire on a range of taxa (vascular plants, invertebrates, reptiles, birds and mammals), with a focus on the influence of the properties of 'fire mosaics' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…2011). Similar results have been obtained in two broader regional surveys: the first, conducted at 280 mallee sites between 2006 and 2008, yielded 17 individuals (Watson et al . 2012, unpublished data), and the second, conducted at 60 mallee sites between October 2007 and March 2008, coincidently also yielded 17 individuals (Val et al .…”
Section: Discussionsupporting
confidence: 84%
“…2011). Similar results have been obtained in two broader regional surveys: the first, conducted at 280 mallee sites between 2006 and 2008, yielded 17 individuals (Watson et al . 2012, unpublished data), and the second, conducted at 60 mallee sites between October 2007 and March 2008, coincidently also yielded 17 individuals (Val et al .…”
Section: Discussionsupporting
confidence: 84%
“…All of these resources were less abundant immediately post-fire and accumulated thereafter, and in most cases changes continued throughout the 56 year post-fire chronosequence. This reiterates findings from studies to the north of our study region (the Mallee Fire and Biodiversity Project [54]), which showed that many habitat attributes continue to change for over a century following fire [19,55]. Also consistent with those and other studies [56][57][58] was the finding that the response of habitat attributes to fire is context dependent-in this instance, different rates of recovery of habitat attributes were apparent in different vegetation types.…”
Section: Does Fire Affect Termite Habitat Resources?supporting
confidence: 90%
“…nov. with Triodia extends beyond the presence vs absence of hummock grass habitat mallee vegetation to a dependence on particular successional stages of development of Triodia hummocks post-fire. Bennett et al (2010) identified the species as being more common in landscapes with large amounts of Triodia Mallee vegetation, with the "time window" for greatest cover of spinifex and presence of large healthy hummocks c. 20-50 years post-fire, with a peak at 35 years (Watson et al, 2012), after which densities decline slowly. In inland southeast Australia Triodia Mallee habitat is fragmented, naturally and through clearing.…”
Section: Discussionmentioning
confidence: 99%